Grass carp MAP3K4 participates in the intestinal immune response to bacterial challenge. Issue 120 (January 2022) - Qu, Fufa; Li, Jialing; Zeng, Xuan; She, Qing; Li, Yurong; Xie, Wenjie; Cao, Shenping; Zhou, Yonghua; He, Zhimin; Tang, Jianzhou; Mao, Zhuangwen; Wang, Yuping; et al.
Abstract: Mitogen-activated protein kinase kinase kinase 4 (MAP3K4) is a multifunctional mediator of the conserved MAPK signaling pathway that plays essential roles in the regulation of immune responses in mammals. However, the function of teleost MAP3K4s in innate immunity, especially in the intestinal immune system, is still poorly understood. In the current study, we identified a fish MAP3K4 homolog ( Ci MAP3K4) in Ctenopharyngodon idella as well as its immune function in intestine following bacterial infection in vivo and in vitro . The open reading frame (ORF) of Ci MAP3K4 encodes putative peptide of 1544 amino acids containing a predicted serine/threonine protein kinase (S_TKc) domain with high identity with other fish MAP3K4s. Phylogenetic analysis revealed the Ci MAP3K4 belonged to the fish cluster and showed the closest relationship to Pimephales promelas . Quantitative real-time PCR (qRT-PCR) analysis revealed that Ci MAP3K4 transcripts were widely distributed in all tested tissues, especially with high expression in the muscle and intestine of healthy grass carp. In vitro, Ci MAP3K4 gene expression was upregulated by bacterial PAMPs (lipolysaccharide (LPS), peptidoglycan (PGN), L-Ala-γ-D-Glu-meso-diaminopimelic acid (Tri-DAP) and muramyl dipeptide (MDP)) and pathogens ( Aeromonas hydrophila and Aeromonas veronii ) in primary intestinal cells. In vivo, the mRNA expression levels of Ci MAP3K4 in the intestine were significantly induced by bacterial MDP challenge in a time-dependent manner; however, this effect could be inhibited by the bioactive dipeptides β-alanyl-l -histidine (carnosine) and alanyl-glutamine (Ala-Gln). Moreover, Ci MAP3K4 was located primarily in the cytoplasm, and its overexpression increased the transcriptional activity of AP-1 in HEK293T cells. Collectively, these results suggested that Ci MAP3K4 might play an important role in the intestinal immune response to bacterial infections, which paves the way for a better understanding of the intestinal immune system of grass carp. Highlights: The first experimental evidence for presence of a functional Ci MAP3K4 gene in grass carp. Transcript levels of Ci MAP3K4 in intestinal cells could be significantly induced by bacterial PAMPs and pathogens . The stimulating effects of MDP on intestinal Ci MAP3K4 expression were inhibited by dipeptides carnosine and Ala-Gln . Ci MAP3K4 is localized mainly in cytoplasm and could enhance transcriptional activities of AP-1-Luc in HEK293T cells.